Analysis Of Information Integrity Of The Instagram Account @Kemenkes_Ri Through The Information Seeking Behavior Theory - Samaatan, Nuriyati; Nurhasanah, Nurhasanah; Aladdin, Yuri Alfrin; Rahmanyta, Fanny (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
Research Objective: This study aims to examine the information integrity of the Instagram account @kemenkes_ri through the variable exposure (X1); Instagram Account Credibility (X2) and the variable Information Needs Fulfillment (Y). Theory: This research uses the Information Seeking Behavior Theory through David Ellis's model. Research Method: the type of research is quantitative, the paradigm used is positivism,The sampling technique used is non-probability sampling, with sample determination using purposive sampling, while the sample size determination uses the Slovin formula with a 10% margin of error and a total of 100 respondents.The questionnaire was distributed via Google Form to the followers of the Instagram account @kemenkes_ri.Analysis was conducted using SPSS version 26. Research Results: This study found that the exposure and credibility of the Instagram account @kemenkes_ri positively influence the variable of information fulfillment for followers.Analysis through the Information Seeking Behavior Theory found that followers seek information through the following stages: [1]starting; [2] chaining; [3] browsing; [4]differentiating [5]monitoring; [6]extracting; [7]verifying; [8]ending. Research Novelty: The novelty in this research focuses on the Instagram account @kemenkes_ri, which provides specific information about health.This explores the impact of exposure and the credibility of the Instagram account @kemenkes_ri on meeting the information needs of followers. satisfaction.